1995
DOI: 10.1007/bf00228922
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound of femoral head cartilage: a new method of assessing bone age

Abstract: This paper analyses the relationship between the thickness of the anterior femoral head cartilage (FHC), as measured by ultrasound, and some anthropometric parameters, such as height, weight, skeletal and chronological age. In addition, it provides standard norms for FHC thickness in a paediatric population. Both hips were examined in 213 consecutive subjects (99 boys and 114 girls), aged 1.9-14 years. Seventy-four subjects underwent hand and wrist X-rays for skeletal maturation: 32 of these were dropped from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…Only few studies have mentioned sonography as an image-guided alternative to examine bone age [3,6,7,24,36]. Wagner et al [36] described a high correlation between sonographic and radiological Risser Grade evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Only few studies have mentioned sonography as an image-guided alternative to examine bone age [3,6,7,24,36]. Wagner et al [36] described a high correlation between sonographic and radiological Risser Grade evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…[12] An alternative approach to evaluation of ossification is US of the overlying cartilage, with the thickness of the anterior femoral head cartilage being shown to be inversely related to chronological age. [10]…”
Section: Discussionmentioning
confidence: 99%
“…Thus, non-ionizing, radiation-based techniques have been developed for the estimation of skeletal age. [101112] Shimura and colleagues measured bone age ultrasonically with Sunlight Bone Age (SBA) and compared the results with radiographs. They showed that good correlation existed with SBA results and TW 2 and CASMAS methods.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, sonographic measurement has broadly advanced in areas such as bone density, but sonographic skeletal maturity measurement has not been widely adopted. Castriota-Scanderbeg et al (5) demonstrated the ability of bone maturity assessment using sonographic evaluation of the thickness of the femoral head articular cartilage. The femoral head articular cartilage thickness is assessed and then translated to bone maturity using values obtained from a healthy Italian population (6).…”
Section: Discussionmentioning
confidence: 99%